Exercise-Generated β-Aminoisobutyric Acid (BAIBA) Reduces Cardiomyocyte Metabolic Stress and Apoptosis Caused by Mitochondrial Dysfunction Through the miR-208b/AMPK Pathway - Yu, Yanan; Chen, Wewei; Yu, Ming; Liu, Jinsha; Sun, Huan; Yang, Ping (Frontiers in Cardiovascular Medicine, 2022)
Methods: In male SD rats (8-week-old), MI was used to induce HF by ligating the left anterior descending branch of the coronary artery. In the Sham group, the coronary artery was threaded but not ligated. After HF development, Sham and HF rats were exercised for 8 weeks and exercise-induced cardiac remodeling after MI were assessed using echocardiography, H&E, Masson and TUNEL staining for the detection of apoptosis-associated factors in cardiac tissue. Mass spectrometry were used to measure BAIBA production. High-throughput sequencing were used to explore its cardioprotective effects. An in vitro model of apoptosis was generated by applying H2O2 to cells to induce mitochondrial dysfunction. In addition, cells were transfected with either a miR-208b analogue or a miR-208b inhibitor. Apoptosis-related proteins were detected by WB. ATP production was also assessed by luminometry. After administration of BAIBA and Compound C, the expression of proteins related to apoptosis, mitochondrial function, lipid uptake, and β-oxidative were determined. Changes in the levels of ATP and ROS were assessed by fluorescence microscopy. In addition, alterations in δψm were obtained by confocal microscopy. Results: Rats with HF are accompanied by mitochondrial dysfunction, metabolic stress and apoptosis. Reduced expression of apoptosis-related proteins was observed, together with increased ATP production and reduced mitochondrial dysfunction in the HFE compared with HF group. Importantly, exercise increased the production of BAIBA. To assess whether BAIBA had similar effects to exercise, rats were treated with 75 mg/kg/ day of BAIBA and we found BAIBA had a similar cardioprotective effect. Transcriptomic analyses found that the expression of miR-208b was increased after BAIBA administration, and subsequent transfection with an miR-208b analogue increased both the expression of apoptosis-related proteins and energy metabolism in H2O2-treated H9C2 cells. In combining transcriptomic with metabolomic analyses, we identified AMPK as a downstream target for BAIBA. Further cell experiments confirmed that BAIBA increased AMPK phosphorylation and had a cardioprotective effect on downstream fatty acid uptake and mitochondrial function, which was prevented by the AMPK inhibitor Compound C. Conclusion: Exercise-generated BAIBA can reduce cardiomyocyte metabolic stress and apoptosis induced by mitochondrial dysfunction through the miR-208b/AMPK pathway.